Assessment of reintegration of ex-Boko Haram/ISWAP terrorists under operation safe corridor in North East Nigeria - Ishaku Hamidu; Nyahama Daniel Bulila (Interdisciplinary Social Studies, 2024)
The study aims to evaluate the reintegration program for former Boko Haram and ISWAP combatants in North East Nigeria. A cross-sectional study was conducted with 500 respondents. Data were collected using a structured questionnaire. The data were analyzed using descriptive statistics. The results indicated that 105 respondents, representing 52.5% agreed that economic, social, and political factors were vital to the success or challenges of the program. They also strongly agreed that less cases of recidivism were a factor affecting the success of the programme. The research contributes to understanding the design of inclusive programs that consider both community and individual needs, aiming to enhance social cohesion and minimize conflict in post-conflict environments. Furthermore, the research on effective communication strategies to inform and engage host communities could shed light on methods to foster understanding and reduce fear regarding ex-combatants. The establishment of independent oversight bodies could be studied to understand their role in monitoring program financing, stakeholder accountability, and resource management.